EVALUASI KUALITAS PELAYANAN HIMBARA TERHADAP PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN DI KOTA AMBON - SAMSON LAURENS (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to analyze the quality of Himbara services and the influence of HR factors and infrastructure facilities for the Harapan Family Program beneficiaries in Ambon City. This research is a descriptive study conducted for independent variables without making comparisons or connecting with other variables. The population in this study were all beneficiary communities of the Family Hope Program in Ambon City in 2019 phases I through phase III of 7,184 KPM. Determination of the sample is purposive sampling with the consideration that the PKH beneficiary community that can be used as respondents are adults, especially pregnant women, as many as 144 pregnant women as one part of the beneficiary community of the Harapan Family Program in Ambon City. The results showed that (1) the quality of Himbara services in terms of tangible dimensions, empathy, responsibility, responsiveness and assurance, (2) HR factors and infrastructure facilities influence the quality of Himbara services for beneficiaries of the Harapan Family Program in Ambon City.